Women's Perspectives on Public Transportation in Jakarta, Indonesia – Reliability and Service Quality Insights - Shamsul Harumain, Yong Adilah; Barus, Lita Sari; Fauzi, Nurfatin (UI Scholars Hub, 2024)
The provision of public transport is of utmost importance in effectively addressing the needs of women residing in developing nations. Nevertheless, it has been noted that the issue of gender-sensitive public transport lacks substantial consideration in the majority of developing nations worldwide. Universal designs are recognised internationally for their rational and economically efficient characteristics, as they accommodate the needs and preferences of not only women but also other individuals who require or desire access to public transportation. Within the realm of public transport, a controversial topic has emerged regarding the introduction of specialised or unique services. The present debate has drawn attention to a number of potential negative effects, such as gender-related stereotypes, insufficient service delivery during times of peak demand, and higher expenses as a result of the requirement for facilities and services that are gender-specific. The primary objective of this study is to investigate the viewpoints of female residents living in Jakarta, Indonesia regarding the reliability of public transport and the quality of its services. In conclusion, our research findings suggest that women living in Jakarta demonstrate an ability to adjust to the available infrastructure, regardless of their social standing and economic conditions, even in cases where these facilities are not specifically designed for women. Nevertheless, it is imperative to acknowledge that services tailored explicitly to address the distinct requirements of women are not only well-received but also enhance their mobility when compared to services that do not integrate these provisions.